Evaluasi Kondisi Fisik Dominan Pada Atlet Motocross Kota Banda Aceh - Karimuddin Karimuddin; Masri Masri; Novi Lidya Isdarianti; Afief Mawazier; Zulfikar Zulfikar; Nurhadi Santoso; Agus Wiyanto (YLPK Mahardhika, 2023)
Motocross is a form of sport that combines the content of a racer with the automotive field or more precisely the engine. This sport is included in the category of extreme sports that require excellent physical condition and a good mentality. In Banda Aceh City there is a Racing Forum whose training ground is located under the Lamnyong bridge, the forum has a Motocross Team. To obtain maximum performance, the physical conditions are very influential so excellent physical conditions are needed. This study aims to determine the dominant physical conditions of motocross athletes in Banda Aceh. A quantitative descriptive approach is used to understand the research data. The population in the study involved Motocross Athletes in Banda Aceh City while the sample used was 6 people with the Total Sampling technique. Data analysis in this study used the calculation of the average value and the calculation of the proportion value. The data collection process is carried out through the tests given. The conclusion from this study is that the dominant physical condition of Banda Aceh Motocross athletes is in the